2020
DOI: 10.21203/rs.3.rs-31062/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of urinary biomarkers of mycotoxin exposure in adults from Cameroon

Abstract: Background In Cameroon dietary staples are contaminated with diverse toxic fungal metabolites, known as mycotoxins. Aflatoxins and fumonisins are of particular public health concern, particularly in relation to cancer and/or early life stunting. Mixtures of these toxins are predicted from food measures, and in this work, the levels and frequencies of urinary mycotoxin biomarkers are reported in Cameroonian adults. Methods A single first void urine sample was collected from 89 adults (aged range: 28–85, male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…In Southern and Central Africa, Shephard et al (2013) evaluated ZEA exposure levels in 54 adult females from South Africa using urine samples: ZEA was detected in all the urine samples with a mean level of 0.529 ng/mg creatinine, while 92% and 72% of the samples contained alpha and beta zearalenol with mean concentrations of 0.614 ng/mg creatinine and 0.702 ng/mg creatinine, respectively. In Yaoundé, Cameroon, Abia et al (2020) collected and analyzed 89 Cameroonian adults' urine for various Fusarium mycotoxins; the authors observed that ZEA and its phase I metabolites were the most frequently detected mycotoxins (82% of the sample analyzed contained detectable quantities of ZEA, alpha zearalenol, and beta zearalenol) with two samples exceeding the EU TDI.…”
Section: Rep Orted E Xp Osure a Ss E Ss Ment And Ris K Char Ac Teriz ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In Southern and Central Africa, Shephard et al (2013) evaluated ZEA exposure levels in 54 adult females from South Africa using urine samples: ZEA was detected in all the urine samples with a mean level of 0.529 ng/mg creatinine, while 92% and 72% of the samples contained alpha and beta zearalenol with mean concentrations of 0.614 ng/mg creatinine and 0.702 ng/mg creatinine, respectively. In Yaoundé, Cameroon, Abia et al (2020) collected and analyzed 89 Cameroonian adults' urine for various Fusarium mycotoxins; the authors observed that ZEA and its phase I metabolites were the most frequently detected mycotoxins (82% of the sample analyzed contained detectable quantities of ZEA, alpha zearalenol, and beta zearalenol) with two samples exceeding the EU TDI.…”
Section: Rep Orted E Xp Osure a Ss E Ss Ment And Ris K Char Ac Teriz ...mentioning
confidence: 99%
“…In Yaoundé, Cameroon, Abia et al. ( 2020 ) collected and analyzed 89 Cameroonian adults' urine for various Fusarium mycotoxins; the authors observed that ZEA and its phase I metabolites were the most frequently detected mycotoxins (82% of the sample analyzed contained detectable quantities of ZEA, alpha zearalenol, and beta zearalenol) with two samples exceeding the EU TDI.…”
Section: Reported Exposure Assessment and Risk Characterization Of Ze...mentioning
confidence: 99%